Organization and dynamics of receptor proteins in a plasma membrane - Koldsø, H; Sansom, M (American Chemical Society, 2015)
The interactions of membrane proteins are influenced by their lipid environment, with key lipid species able to regulate membrane protein function. Advances in high resolution microscopy can reveal the organisation and dynamics of proteins and lipids within living cells at resolutions < 200 nm. Parallel advances in molecular simulations provide near-atomic resolution models of the dynamics of the organisation of membranes of in vivo like complexity. We explore the dynamics of proteins and lipids in crowded and complex plasma membrane models, thereby closing the length and complexity gap between computations and experiments. Our simulations provide insights into the mutual interplay between lipids and proteins in determining mesoscale (20 to 100 nm) fluctuations of the bilayer, and in enabling oligomerization and clustering of membrane proteins.